Factors affecting browsing duration on a health discussion forum : analysis of eye-tracking data - Pian, Wenjing (2020)
Introduction: User-contributed information on health-related social media sites contains useful user-experience information that complements information on authoritative health information websites. Though more people are searching and browsing social media sites for health information, there are few studies of user browsing behaviour on these sites, and the factors that affect the behaviour. This study investigated the factors affecting the users’ skimming and examining durations when browsing a health discussion forum. Methods: An eye-tracker system was used to record users’ eye fixations and eye movements when browsing a health discussion forum, HealthBoards.com.Analysis: Stepwise multiple linear regression was used to develop models to predict users’ skimming and examining durations. Results: The type of health information need context (i.e. browsing for own health issue, browsing for someone else’s health issue, and browsing with no particular health issue in mind), the perceived urgency of the health information need, and the length of the health information text were found to be significant predictors of the examining and skimming durations. Demographic factors of gender and age were not significant. Conclusion: Future studies of online health information seeking should take these three factors into consideration, and distinguish between browsing two types of screens—the summary screen of document surrogates and the detailed content screen.